Thickness-modulated passivation properties of PEDOT:PSS layers over crystalline silicon wafers in back junction organic/silicon solar cells. (22nd February 2019) - Zhang, Longfei; Wang, Zilei; Lin, Hao; Wang, Wei; Wang, Jiajia; Zhang, Huan; Sheng, Jiang; Wu, Sudong; Gao, Pingqi; Ye, Jichun; Yu, Tianbao
Abstract: PEDOT:PSS/silicon heterojunction solar cell has recently attracted much attention due to the fact that it can be simply and cost-effectively fabricated. It is crucial to suppress the interfacial recombination rate between silicon (Si) and organic film for improving device efficiency. In this study, we demonstrated a thickness-dependent passivation effect, i.e. the passivation quality over Si substrate was promoted dramatically with increasing the thickness of PEDOT:PSS layer. The effective minority carrier lifetime increased from 32 μ s for 50 nm to 360 μ s for 200 nm, which corresponds to a change in implied open circuit voltage ( V oc-implied ) from 545 to 635 mV. Back-junction hybrid solar cells featuring PEDOT:PSS films at rear side were designed to enable adoption of thick PEDOT:PSS layers without having to worry about parasitic absorption, showing a power conversion efficiency (PCE) of 16.3%. Combined with a proper pre-condition on the Si substrate, the back-junction hybrid solar cell with 200 nm PEDOT:PSS layer received an enhanced PCE of 16.8%. In addition, the improved long-term stability for the back-junction device was also observed. The PCE remained 90% (unsealed) after being stored in ambient atmosphere for 30 days and over 80% (sealed) after 150 days.